A case report of diffuse large B-cell lymphoma and gastric signet ring cell adenocarcinoma in the same anatomic site: a clinical and management conundrum - Nwokeocha, Steve Oguguo; Gopalakrishnan, Jeyavishnupriya; Khatiwada, Dikshya; Chaudhary, Ashlesha; Soni, Rajat; Bleik, Pavel; Patel, Anush V. (Journal of Gastrointestinal Oncology; Vol 17, No 3 (June 29, 2026): Journal of Gastrointestinal Oncology, 2026)
Background: Gastric adenocarcinoma is infrequently associated with synchronous or metachronous second malignancies. Even more rare is the presence of two cancers within the same anatomical site. It is unclear if an association exists between the development of diffuse large B-cell lymphoma (DLBCL) and gastric signet ring cell adenocarcinoma (SRCC). We present a case of a woman who presented with both malignancies.Case Description: We present a 67-year-old woman with a complex past medical history including a Roux-en-Y gastric bypass who presented with abdominal pain and profuse diarrhea. Initial endoscopy images did not show signs of obvious malignancy, but subsequent random biopsies from the gastric pouch demonstrated SRCC. Staging imaging and procedures did not show metastases or nodal involvement, so she was subsequently diagnosed with Tumor, Node, Metastasis (TNM) stage 1A gastric SRCC. She had total gastrectomy with esophagojejunostomy. Post-surgical biopsies showed DLBCL of the gastric pouch. The prior SRCC was not noted despite extensive sampling of the resected specimens. She was treated with six cycles of chemoimmunotherapy with rituximab, cyclophosphamide, doxorubicin, vincristine, and prednisone (R-CHOP) for the DLBCL. Subsequent scans showed a new renal mass, but she passed away before further investigations could be done.Conclusions: A potential association exists that led to the development of SRCC and DLBCL in the same anatomical site in our patient. We highlight how this challenging case was managed, and the various unusual aspects.